Morphological Intervention for Students With Limited Vocabulary Knowledge: Short‐ and Long‐Term Transfer Effects. Issue 3 (25th October 2020) - Gellert, Anna S.; Arnbak, Elisabeth; Wischmann, Signe; Elbro, Carsten
Abstract: Students with limited vocabulary knowledge are at high risk for reading comprehension difficulties. Previous studies have found that teaching morphology may support vocabulary growth. In the present study, the authors aimed to replicate and extend these findings by investigating both immediate and long‐term transfer effects to untaught words and untaught pseudowords with well‐known root morphemes. Fifth‐grade students ( N = 332) were randomly assigned to a morphological intervention, an alternative vocabulary intervention, or a control condition. The morphological intervention was found to produce large short‐term effects with respect to the students' abilities to segment and explain both taught and untaught words containing taught morphemes, and medium effects on explanations of likely meanings of pseudowords with well‐known root morphemes. Medium to large effects were still present 10 months later with taught words and transfer words. Training had a small effect on reading comprehension with trained words but no effect on standard measures of reading comprehension or vocabulary.